Clima organizacional: uma análise bibliométrica da produção acadêmica nacional - Gomes Neto, Pedro Paulo (Universidade Federal Rural do Semi-Árido, 2017)
The present work had as objective to make a bibliometric study on the production of national academic articles on organizational climate. The identification of the journals and their classification was obtained in the Sucupira platform. We selected 31 articles from 23 journals between 2007 and 2017, classified with Qualis from A2 to B2. The A1 extract had no national newspaper. The results indicate that the B2 extract has the largest number of journals and publications, with 2011 having the highest concentration of articles. The largest concentration of publications per Institution is located in the UNB, with Silvio Roberto Stefano the author with the highest number of co-authorizations. The most cited author in the publications is Benjamin Schneider and the most used reference was "Construction and validation of a scale of measurement of organizational climate" authored by Maria do Carmo Fernandes Martins. The international journals presented themselves as the most used reference type among the articles. The most relevant words within the articles are: Relationships, satisfaction, environment, culture, performance, perception, people, quality and development.
Keywords: Clima organizacional; Bibliometria; Produção Acadêmica; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO